The Assessment of Paddy Soil Fertility Status Based Soil Fertility Index (SOFIX) in Tuban Indonesia - Abd Aziz Amin; Lutfi Nimatus Salamah; Attabik M Amrillah; Hideki Okuda; Andi Kurniawan (Jurnal Ilmu Lingkungan, 2025)
Rice is one of the main agricultural commodities cultivated by farmers in Tuban Regency, Indonesia. To improve rice productivity, evaluating soil fertility is essential for determining appropriate and balanced fertilization. This study aimed to assess the fertility status of paddy soils in Tuban Regency using the Soil Fertility Index (SOFIX) method to identify nutrient constraints and recommend suitable management practices. Soil samples were collected from agricultural areas integrated with organic farming systems. The results showed low bacterial number and weak nitrogen and phosphorus circulation activities. Chemical parameters, including total carbon, total potassium, total nitrogen, and total phosphorus, were also below optimal levels. These findings indicate that the paddy soils in Tuban Regency are in a low-fertility condition. Therefore, the application of organic materials is recommended to enhance microbial activity, improve nutrient cycling, and restore soil fertility for sustainable rice production.